Development of Halal Tourism to Improve The Community Economy in The Halal Tourism Village of Setanggor - Amalia, Riski; Kartono, Drajat Tri; Wibowo, Agung; Syiam, Nazilatus (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
This study aims to describe the development of the halal tourism village in Setanggor. It employs a qualitative method with a descriptive approach. The findings indicate that the development of halal tourism in Setanggor involves empowerment through the active participation of the community and the role of the village government. This concept is also referred to as Community Based Tourism. Setanggor's Halal Tourism Village was formed by integrating the ideas of village tourism, halal tourism, local wisdom, characteristics of resources, and uniqueness possessed by Setanggor's Halal Tourism Village, thus creating innovations in the development of halal tourism in rural areas. In its management, Setanggor's Halal Tourism Village offers products that adhere to Islamic principles. Community participation in managing Setanggor's halal tourism village is reflected in the creation of employment opportunities after the village becomes a tourist destination, thus positively impacting the welfare of the local community.